PENJATUHAN SANKSI PIDANA TERHADAP ANGGOTA KEPOLISIAN YANG KARENA KEALPAANNYA MENYEBABKAN KORBAN MENINGGAL: The Imposition of Criminal Sanctions on Police Officers Whose Negligence Results in the Death of a Victim - Benedict Veby Cristie Renyaan; Sutrisno (Faculty of Law, Trisakti University, 2025)
Every citizen, including members of the police force, holds equal status before the law, including when involved in actions that result in criminal liability due to negligence. The issues discussed in this research concern the judge's considerations in imposing criminal sanctions for negligence causing death by a police officer, as well as the application of criminal liability for such negligence in Decision Number 55/Pid.B/2024/PN Plk based on Article 359 of the Indonesian Criminal Code (KUHP). The research method used is normative legal research with a descriptive-analytical approach, utilizing secondary data and drawing conclusions through deductive reasoning. The result concludes that Decision Number 55/Pid.B/2024/PN Plk affirms that police officers can be held criminally liable for negligence resulting in death, as regulated in Article 359 of the KUHP. Although the offender acted in the context of duty, the element of negligence remains the basis for imposing criminal sanctions. This decision reflects the application of the principle of equality before the law and serves as an important precedent in upholding the rule of law and accountability of law enforcement officers.